ANALYSIS OF FACTORS INFLUENCING NETFLIX APPLICATION CUSTOMER LOYALTY IN GENERATION Z - Adinda Lubis; Juwita Samaria Manurung; Didik Gunawan; Nursaimatussaddiyah (RADJA PUBLIKA, 2025)
This study analyzes the role of price, brand image, and E-service quality factors in shaping Generation Z customer loyalty towards Netflix services. Using a quantitative method with a sample of 96 respondents from Generation Z (aged 18-27 years), data were collected through an online questionnaire and analyzed with SMART PLS 3.0. The results showed that price has a significant effect on customer loyalty, while brand image and E-service quality do not have a significant effect. These findings confirm that the right pricing strategy can increase customer loyalty, and factors such as content diversity and ease of use of the platform are more dominant in retaining Generation Z customers.